IMPLEMENTATION OF KIDS ATHLETICS AT THE NATIONAL STUDENT SPORTS OLYMPIAD (O2SN) FOR PJOK ELEMENTARY SCHOOL TEACHERS IN DUREN SAWIT DISTRICT - Moch Asmawi; Samsudin; Iwan Setiawan; Mustara; Arifka Fadil Muhammad; Elly Diana Mamesah; Arisman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract As physical education teachers at the elementary school level, we must understand about kids athletics because this is the basis for providing basic movements to students at school. Then physical education teachers must also understand the mechanism and techniques in organizing athletic sports competitions at the elementary school level. In addition, some coaches and physical education teachers have not been able to maximize training tools or simple training media to be given to athletes or students through training programs. Therefore, this community service program is an effort to disseminate knowledge from the University to the community, especially physical education teachers and sports coaches, especially athletics in East Jakarta City so that they have a lot of proper and fun physical activities. Abstrak Sebagai guru pendidikan jasmani tingkat sekolah dasar kita harus memahami tentang atletik anak karena ini merupakan dasar dalam memberikan gerak dasar kepada siswa di sekolah. Kemudian guru pendidikan jasmani juga harus memahami mekanisme dan teknik dalam penyelenggaraan pertandingan olahraga atletik di tingkat sekolah dasar. Selain itu, sebagian pelatih dan guru pendidikan jasmani belum mampu memaksimalkan alat latihan atau media latihan sederhana untuk diberikan kepada atlet atau siswa melalui program latihan. Oleh karena itu, program pengabdian kepada masyarakat ini merupakan salah satu upaya untuk menyebarluaskan ilmu pengetahuan dari Universitas kepada masyarakat khususnya para guru pendidikan jasmani dan pelatih olahraga khususnya atletik di Kota Jakarta Timur agar banyak melakukan aktivitas jasmani yang baik dan menyenangkan.